MANTRA PENGOBATAN DAN IDENTITAS BUDAYA: KAJIAN DI KALANGAN MASYARAKAT SUKU DAYA KABUPATEN PASER - Wahdini, Chintya; Putri, Nina Queena Hadi (JURNAL SKRIPTA, 2025)
ABSTRACT Medical mantras are part of the oral tradition of the Dayak people which not only functions as a healing method, but also reflects their cultural identity. This study aims to analyze the role of treatment mantras in the lives of Dayak people as well as reveal the cultural values contained in them. The research method used is a qualitative method with an ethnographic approach, which involves observation and in-depth interviews with practitioners of traditional medicine, such as belian who still use mantras in their daily lives. The results showed that treatment mantras in Dayak society have four main aspects that reflect their cultural identity (1) aspects of spiritual beliefs, where mantras are believed to have magical powers to expel diseases or poisons; (2) relationship with nature, where it is believed that mantras can order diseases to return to the land, sky, water, or their place of origin, and it means that human health depends on the balance of the ecosystem; (3) social system and community solidarity, which indicates that traditional medicine is not only centered on the individual but also involves family support and the role of belian as spiritual leader and healer; (4) language and oral tradition reflected in the repetitive and symbolic structure of mantras, as well as the role of the Dayak language as part of the cultural heritage passed down through generations. Keywords: Medical mantras, cultural identity, Dayak tribe, traditional beliefs, Dayak language, traditional medicine.